Factor Structure, Measurement Invariance, and Abbreviated Versions of The Adolescent Dissociative Experiences Scale (A-DES). Issue 4 (8th August 2022) - Lindfors, Kristiina Ulla Maarit; Therman, Sebastian; Lindgren, Maija; Kekkonen, Virve; Tolmunen, Tommi
ABSTRACT: The purpose of this study was to examine the factor structure of the Adolescent Dissociative Experiences Scale (A-DES) questionnaire with item response theory (IRT) methods, including an assessment of measurement invariance with differential item functioning (DIF) analysis. Three abbreviated versions of the A-DES (with 20, 10, and 5 items) were constructed based on the IRT and DIF statistics. The respondents in this population-based study (N = 4, 072) were 12- to 19-year-old Finnish junior and senior high school students. A one-factor model of the A-DES was best supported, and the original theoretical four-factor model showed poor fit. The A-DES turned out to have high measurement invariance with respect to age, gender, transgender tendencies, having multiple friends, the use of illegal substances, and experience of being bullied. Compared to the full 30-item A-DES, abbreviated versions of the questionnaire retained acceptable information value and empirical reliability in the clinically relevant range of symptomatology. Further psychometric studies are needed especially with regards to clinical use.